RELATIONSHIP BETWEEN PSYCHOLOGICAL, INCENTIVES AND AVAILABILITY OF FACILITIES WITH PERFORMANCE OF THE TUBERCULOSIS CONTROL PROGRAMME - Dian Rosadi; Fauzie Rahman; Sasikarani Sasikarani (Jurnal Berkala Kesehatan, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. The achievement of Pulmonary TB CDR in the working area of Banjarmasin City Health Office is still 49% in 2015 and increased by 52% in 2016. The low achievement of pulmonary TB CDR in Banjarmasin became a health problem related to the performance of P2TB officers in the Health Service Working Area City of Banjarmasin. This study aims to explain factors related to the performance of Proram Control Officers Tuberculosis in the Work Area of Banjarmasin City Health Office. This research is a quantitative research using cross sectional design. The population is all officers of P2TB in the working area of Banjarmasin City Health Office. The sample taken is a population of 57 people using total sampling technique. The results showed that the availability factor of the facility was related to the performance of the Proram Control Officer Tuberculosis (ρ-value = 0.049). While factors unrelated to officer performance are psychological factor (ρ-value = 1.000) and incentive (ρ-value = 0.260). The Conclusion of this study is the relationship between the availability of facilities with the performance of Proram Control Officers Tuberculosis, but there is no relationship between the psychological and incentives with the Proram Control Officer Tuberculosis in the Work Area of Banjarmasin City Health Office.